Literature Study on the Application of the Talking Chips Learning Model to the Learning Competency of High School Students - Lucy Petra Kamelsa; Ristiono Ristiono; Heffi Alberida; Relsas Yogica; Zulyusri Zulyusri (Bioeducation Journal, 2021)
There are not many articles that discuss the application of the Talking Chips type cooperative learning model or also known as the jingling buttons in the study of Biology, there are differences in the dependent variables discussed in each article and there has been no research with a literature study on the effect of applying the cooperative learning model type. Talking Chips on the learning competence of SMA/Vocational High School students became the background of the researcher in writing this thesis. The purpose of this study was to determine the effect of applying the Talking Chips learning model on the learning competence of SMA/SMK students based on a literature study. The type of research used is literature study research which refers to the research conducted previously. The data used in the form of secondary data in the form of articles in journals that have been accredited by SINTA and related to the application of the Talking Chips type cooperative learning model to the learning competencies of SMA/SMK students. The research sample is all sample members who are applied with the Talking Chips type cooperative learning model contained in the specified article.Learning by using the Talking Chips model is able to improve the learning competence of students in the aspects of knowledge competence, attitude competence, and skill competence. It is hoped that this research can be a source of information and reference in the use of the Talking Chips learning model so that effective learning can be carried out.